Return on process (ROP) getting real performance results from process improvement - West, Michael (Auerbach Publications, 2016)
Although there are countless books about process improvement and business performance, there is a dearth of literature on how process improvement yields business performance results. Filling this need, "Return On Process (ROP): Getting Real Performance Results from Process Improvement" provides strategic and tactical guidance on how to achieve a positive ROP. The book details a comprehensive and coherent end-to-end process for integrating organizational performance objectives and measures to process improvement activities. Describing how to achieve real business performance results from process improvement, it supplies sound, proven advice on how to improve your organization's software and systems development and delivery processes in ways that affect your business. Defining the relationship between performance and process, the book presents metrics for business performance and explains how to set performance and process improvement goals, measure process improvement results, and lead a performance culture.
Keywords: Reengineering (Management); Performance; Performance technology; Task Performance and Analysis; Réingénierie organisationnelle; Rendement au travail; Instructional and educational works; Matériel d'éducation et de formation